MEMBANGUN PERILAKU ENTREPRENEUR PADA MAHASISWA MELALUI ENTREPRENEURSHIP EDUCATION - Dwi Wahyu Pril Ranto (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2016)
Entrepreneurship education has an important role in changing the mindset of students. Entrepreneurship education is given to students because it can change the mindset of students, during which only interest as a job seeker to students who are ready to create jobs. Given this entrepreneurship education, besides being able to change the mindset of students, is also expected to change student behavior. The behaviors are the achievement motivation, unyielding, the courage to take risks, creative and innovative. To realize the student mindset change is necessary as well as the role of universities in the implementation of entrepreneurship education. In addition, the role of college graduates in motivating young graduate being an entrepreneur is very important in growing the number of entrepreneurs. With rising entrepreneurs from among the scholars will reduce the growing number of unemployed and even increase the number of jobs. Keywords : Enterpreneurship, Enterpreneurship Education, Enterpreneurship BehaviorsEntrepreneurship education has an important role in changing the mindset of students. Entrepreneurship education is given to students because it can change the mindset of students, during which only interest as a job seeker to students who are ready to create jobs. Given this entrepreneurship education, besides being able to change the mindset of students, is also expected to change student behavior. The behaviors are the achievement motivation, unyielding, the courage to take risks, creative and innovative. To realize the student mindset change is necessary as well as the role of universities in the implementation of entrepreneurship education. In addition, the role of college graduates in motivating young graduate being an entrepreneur is very important in growing the number of entrepreneurs. With rising entrepreneurs from among the scholars will reduce the growing number of unemployed and even increase the number of jobs. Keywords : Enterpreneurship, Enterpreneurship Education, Enterpreneurship Behaviors